The Effect of Seawater Exposure on Osmoregulation Physiology in Gourami Fish (Osphronemus goramy) - I Wayan Merta; Kusmiyati Kusmiyati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Fundamentally, osmoregulation is a complex physiological process that functions to regulate the concentration of body fluids, including the balance of water and electrolytes (ions), in order to remain in a state of homeostasis even when the external environment experiences dynamic fluctuations. This study aims to analyze the effect of seawater exposure on the osmoregulatory physiology of gourami fish (Osphronemus goramy) through observations of survival endurance at various seawater concentrations. This research is an experimental study, with one control group and three treatment groups, each treatment group replicated 10 times. The parameter observed is the duration of survival of the gourami fish in each treatment. The data were analyzed using ANOVA and further tested with the Games-Howell test. The results of the study indicate that there is a significant effect of seawater exposure on the osmoregulatory physiology of gourami fish (p < 0.05). This study concludes that there is a significant effect of seawater exposure on the osmoregulatory physiology of gourami fish (Osphronemus goramy). Increasing seawater concentration causes a significant decrease in the survival rate of gourami fish.